THE INFLUENCE OF THE NUMBER OF TOURIST VISITS, TOURIST ATTRACTIONS, OCCUPANCY LEVELS ON ORIGINAL REGIONAL INCOME IN THE SARBAGITA REGION - I Gusti Agung Gede Agung Anandita Kamasan; Made Heny Urmila Dewi (Adisam Publisher, 2024)
Tourism is one sector that has the ability to cause rapid economic change. The progress of the tourism sector has a positive impact on its contribution to regional income. The aim of this research is to provide empirical evidence regarding the influence of the number of tourist visits, number of tourist attractions and occupancy levels on local original income (PAD). This research was conducted on PAD in the Denpasar, Badung, Gianyar and Tabanan areas using secondary data obtained from the Central Statistics Agency. The number of observations in this research uses panel data, namely a combination of time series data and cross section data. The time series data used is data for each year starting from 2012-2023 (10 years). Meanwhile, the cross section data used is three districts and one city, namely Denpasar City, Badung Regency, Gianyar and Tabanan. So, the number of observations in this study was 40 observations. The data analysis technique in this research is multiple linear regression analysis. The results of the research show that the number of tourist visits, number of tourist attractions and occupancy levels have a partial and simultaneous positive effect on local original income in the Sarbagita region.